Analisis Konflik Politik Pasca Pembentukan Daerah Otonomi Baru - Lukman Rais; Umar Ramli; Wahyudin Halik; Uswatul Mardliyah; Nur Hidaya (Department of Sociology, Faculty of Social and Political Sciences, Universitas Andalas, 2023)
This research aims at analyzing auses and impacts of political conflicts, as well as changes in the governance structure and conditions following the establishment of new autonomous regions. The study employs a mixed methods approach using an exploratory sequential design. The research is conducted in Sorong City, Southwest West Papua Province, utilizing cluster random sampling. Data collection techniques involve questionnaires, observations, interviews, document analysis, and triangulation. Data analysis follows an explanatory sequential mixed methods approach, involving descriptive statistical analysis and qualitative analysis. The research findings indicate that the causes of political conflict are attributed to changes in regional governance and power redistribution stemming from polarization based on social and cultural differences, as well as differences in political views and ideologies leading to conflicts among elite political parties competing for power. The impact of these conflicts has resulted in the instability of governance and hindered government decision-making, prompting government efforts to address these issues through dialogue and communication, with civil society playing a role as pressure groups and peace agents. Furthermore, there have been no structural changes in governance because the new autonomy policy primarily aims at political objectives to mitigate conflicts, with economic and administrative goals not yet being the primary focus. Additionally, the condition of governance is in the process of improvement as the new government is engaged in restructuring and infrastructure development, thus making the governance condition currently unstable.